Assessment of ground water pollution in Itagunmodi, South-West, Nigeria (2012)
Some investigations have been earned out on geochemical characteristics of soil samples that embedded the ore deposits. Physiochemical analysis of water collected within gold mining area and the water consumed in the town of Itagunmodi was earned out to determine their hygienic conditions. The major objective of this study was to determine the suitability of the available water consumed in the town based on the Physiochemical analysis test carried out. In this regards, four major sources of water were analyzed. Analysis shows that the water within the town of Itagunmodi was hygienic with the inclusion of water within the mining site. The analysis includes; conductivity test, the pH test and others. It was noticed that the pH of the sample from the gold mining site was also suitable for drinking according to the World Health Organization standard. For a safe drinking water, the pH should be between (6.5 -8.5).